Analisis Kritis Kebijakan Hilirisasi Kelapa Sawit Indonesia - Novyandra Ilham Bahtera; Manuntun Parulian Hutagaol; Harianto Harianto (Faculty of Economics and Bussiness, Universitas Diponegoro, Semarang, Indonesia, 2025)
Indonesia's palm oil industry is a key pillar of the national economy, contributing significantly to exports and downstream industrial development. To encourage downstreaming, increase product added value, and reduce dependence on raw material exports, the government implemented a Crude Palm Oil (CPO) export levy policy. This study analyzes the impact of this policy on exports, domestic processing capacity, and the competitiveness of palm oil products using a literature review and qualitative descriptive analysis. The results show that the export levy policy has succeeded in increasing the proportion of high-value-added processed exports, such as biodiesel and oleochemicals, while also boosting domestic industrial capacity, job creation, and foreign exchange earnings. However, a negative outcome has been the decline in export market share for raw CPO, reflecting that the transition to processed products remains suboptimal. Additionally, challenges such as non-tariff barriers, international price fluctuations, and global competition continue to affect policy implementation. In conclusion, to enhance the effectiveness of downstreaming policies, it is necessary to strengthen investment in processing technology, diversify export markets, and implement sustainability practices. These strategic steps are expected to improve global competitiveness, support the long-term sustainability of the Indonesian palm oil industry, and deliver more optimal economic benefits over time. This study contributes to the literature by providing a comprehensive upstream–downstream assessment of Indonesia’s CPO export levy policy, highlighting its role in promoting downstreaming and value-added exports while revealing persistent structural and competitiveness challenges.